Posting purchases on social media increases happiness: the mediating roles of purchases' impact on self and interpersonal relationships. Issue 5 (14th August 2017) - Duan, Jingyi; Dholakia, Ruby Roy
Abstract : Purpose: The purpose of the present research is to investigate how consumers' purchase posting behavior on social media influences their own happiness. Design/methodology/approach: The paper presents three studies. Study 1 was an experiment that manipulated purchase and posting behavior. Studies 2 and 3 utilized surveys which asked participants to report their actual purchases and posting behaviors. Data were examined using regression and bootstrap mediation analysis. Findings: Posting purchases on social media has a positive influence on consumers' happiness through the mediating roles of perceived impact of purchases on self and interpersonal relationships. Research limitations/implications: This paper contributes to the research on social media by demonstrating that because of its remarkable characteristics, posting purchases on social media significantly increases consumers' happiness. It fills the research gap of how word-of-mouth and conspicuous consumption influences the storyteller's happiness. It is also the first research which suggests that user-generated content of purchases actually can be a new carrier of conspicuous consumption. The findings shed light on the substantial influences of posting purchases on the use/consumption stage of consumer behavior. Practical implications: Because posting purchases on social media increases consumers' happiness, marketers can develop strategies to encourage consumers to post about their purchases more. Originality/value: To the best of the authors' knowledge, this research is the first to demonstrate the positive effect of social media purchase posting on consumers' happiness and identify the mechanism under which this effect occurs.